Integration of Sustainable Development Goals and Media Literacy in Education - Kostenko, Anastasiia; Kuzmenko, Oksana (Studia Warmińskie, 2023)
This article explores the urgent need for integrating media literacy and Sustainable Development Goals (SDGs) into the educational process, especially in the face of increasing information warfare and technological changes. The authors argue that media literacy is not only a skill but a crucial tool for ensuring critical thinking and social stability. They emphasize the role of educators as primary "operators" of information and discuss how improved media literacy can make educational systems more resilient against external threats. Utilizing an interdisciplinary approach, the article aims to develop effective systems for bolstering the media literacy of educational staff as a pathway to achieving specific Sustainable Development Goals.